It fell from the sky - Fan, Terry (Frances Lincoln Children's Books, 2022)
"It fell from the sky on a Thursday. None of the insects know where it came from, or what it is. Some say it's an egg. Others, a gumdrop. But whatever it is, it fell near Spider's house, so he's convinced it belongs to him. Spider builds a wondrous display so that insects from far and wide can come to look at the marvel. Spider has their best interests at heart. So what if he has to charge a small fee? So what if the lines are long? So what if no one can even see the wonder anymore? And what will Spider do after everyone stops showing up?"--Provided by publisher